PENGAWASAN PEMBANGUNAN SUPERMARKET KECAMATAN SOMBA OPU KABUPATEN GOWA - Meiswari, Arinda; Ansari, Muhammad Isa; Usman, Jaelan (Universitas Muhammadiyah Makassar, 2024)
This study aims to find out how the government collaborates in supervising the construction of supermarkets such as department stores. This type of research uses qualitative research. Data collection techniques are through observation, interviews, documentation, and media reviews. The results of the study show that the supervision of the construction of the Supermarket, Department Store and One Sama in Somba Opu District, Gowa Regency has not fully gone well. Because the existence of supermarket buildings in Gowa Regency must pay more attention to Presidential Decree no. 112/2007 Article 4 Paragraph 1: Concerning the establishment of shopping centers and modern shops which must take into account the socio-economic conditions of the community, the existence of traditional markets, small and medium enterprises in the area concerned. So that the existence of the supermarket building does not harm the small kiosks in the vicinity